PENGARUH KOMUNIKASI TUGAS TERHADAP VITALITAS YANG DIMODERASI OLEH OTONOMI PEKERJAAN - Alan Frimanto Eliambu (Jurnal Bisnis dan Kewirausahaan, 2021)
This study aims to examine The influence of task communication on vitality employed moderated by job autonomy. The data were obtained from the questionnaires distributed to Hospital employees Jiwa Surakarta and Hospital PKU Muhammadiyah Surakarta. The sampling technique used is cluster sampling with a population of 150 hospital employees. Hypothesis testing is performed using regression analysis using SPSS 18.The results of this study indicate that task communication has a significant effect on vitality employees and job autonomy moderates relationship between task communication and vitality employees. Keywords : vitality employees, task communication, job autonomy